[Moyamoya disease] - Papanagiotou, P; Grunwald, I; Politi, M; Roth, C; Reith, W (2005)
Moyamoya disease is an idiopathic progressive vasculopathy characterized by slowly progressive narrowing involving the distal internal carotid artery and the proximal circle of Willis. Collateral vessels develop to compensate for the slowly progressive stenosis. These enlarged collaterals appear as a "puff of smoke" on angiography, which gives the disease its name. This review discusses the clinical manifestation, imaging findings, and angiographic features.